'A New Kind of Rays': Gothic Fears, Cultural Anxieties and the Discovery of X-rays in the 1890s. Issue 1 (1st May 2015) - Avery, Simon
<x xml:space="preserve">Abstract</x> In 1895, the world of modern physics was effectively ushered in with the discovery of X-rays by the German physicist, Wilhelm Conrad Röntgen. X-rays rapidly changed the ways in which the human body was perceived, and their discovery was documented and fiercely debated in scientific articles, newspaper reports, literary writings, cartoons and films. This article examines a range of these responses, both 'scientific' and' popular', and considers the particular significance of their repeated recourse to the Gothic and the uncanny as a means of expressing both excitement and disquiet at what the new X-ray phenomenon might mean.